2022
DOI: 10.1007/s00167-022-06937-0
|View full text |Cite
|
Sign up to set email alerts
|

High return to sports and return to work rates after anatomic lateral ankle ligament reconstruction with tendon autograft for isolated chronic lateral ankle instability

Abstract: Purpose To evaluate clinical outcomes as well as return to sports (RTS) and return to work (RTW) rates following anatomic lateral ankle ligament reconstruction with a tendon autograft for chronic lateral ankle instability (CLAI) in a high-risk population, and to compare these outcome parameters between patients having received a gracilis tendon autograft (GT) and free split peroneus brevis tendon (PBT) autograft. Methods Twenty-eight consecutive patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This has many disadvantages, such as a large surgical incision, influence on the function of other tendons, change of the normal structure of the lateral malleolus, and ankle joint ROM restriction. After ligament reconstruction with an autologous tendon[ 75 ], work and sports can be quickly resumed. However, due to the change in the normal anatomical structure of the ankle ligament, postoperative complications, such as ankle joint activity restriction and strain pattern change, are often observed[ 76 ].…”
Section: Management Measuresmentioning
confidence: 99%
“…This has many disadvantages, such as a large surgical incision, influence on the function of other tendons, change of the normal structure of the lateral malleolus, and ankle joint ROM restriction. After ligament reconstruction with an autologous tendon[ 75 ], work and sports can be quickly resumed. However, due to the change in the normal anatomical structure of the ankle ligament, postoperative complications, such as ankle joint activity restriction and strain pattern change, are often observed[ 76 ].…”
Section: Management Measuresmentioning
confidence: 99%
“…In clinical practice, conservative treatment is initially recommended for CLAI, with surgery being considered if symptoms do not improve or worsen after 3-6 months of conservative treatment. The surgical techniques include anatomical repair [8][9] , anatomical reconstruction [10][11] , and non-anatomical reconstruction [12][13] . Anatomic repair of the ATFL offers advantages such as minimal surgical trauma, simplicity in operation, and favorable postoperative recovery; thus it is currently regarded as the preferred choice for repairing the ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical treatment options have been described to restore ankle stability [ 31 , 40 ]. Repair of ankle ligaments with a modified Broström–Gould procedure, consisting of lateral ligament imbrication with direct suture repair and transfer of the extensor retinaculum, remains the current gold standard for surgical management of CLAI [ 29 , 40 ]. However, it has been reported that 25% of patients are unable to return to sport [ 7 , 12 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%